Design Smart Classroom Based IoT at SMP Ali Bin Abi Tholib - Ismael; Siregar, Arfanda Anugrah; Sari, Dewi Comala (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
A classroom is a room that functions as a place for teaching and learning activities. In the classroom there are also various tools to support teaching and learning activities such as tables, whiteboards and other electronic equipment. The importance of using technology in teaching and learning classrooms is because current needs are increasing with the times.Smart Classroom is a technology that makes the class have an automation system with very sophisticated performance. This system utilizes technology that can control electronic equipment in the classroom automatically. The high level of negligence of electronic device users in turning off electronic items that are often on continuously, such as lights, air conditioners, projectors, results in wastage of electrical energy. To overcome this problem, researchers built an automation system in classrooms using the IoT system. The research method used is an experimental model. This automatic system is programmed by the Arduino application by creating a security system using Radio Frequency Identification (RFID) as the radio frequency data carrier that will be received by the receiver. The results of this research are a smart classroom prototype using RFID that can operate well. The RFID sensor's ability to detect the ID between the Card and Reader is a maximum distance of 1cm. The Reader's ability to detect ID cards takes 2 to 3 seconds from when the ID card is attached to the Reader and this tool will work when the user attaches the RFID to the reader so that all connected equipment will automatically turn ON such as lights, AC and projectors.